2020
DOI: 10.1088/1742-6596/1554/1/012033
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Realistic Mathematics Education Approach Oriented Higher Order Thinking Skills to Achievements’ Calculus

Abstract: The goal of this research is to determine the influence of the realistics mathematics education (RME) approach by oriented higher order thinking skills (HOTS) on the results of students’ mathematics learning on the subject of the calculus in SMAN 10 and SMAN 12 Padang. The method used is the experimental research with pre and post-test design randomized control group. The data analysis technique used is the test for normality and homogeneity test followed by using a t-test. The results revealed that there were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 2 publications
3
8
0
4
Order By: Relevance
“…So the students' mathematical concept understanding ability becomes better. In line with the results of Purwati (2020) and Arnellis et al (2020) showed that the use of RME can improve student learning outcomes. Strengthened by some research results according to Tamur, Juandi, and Adem (2020), Febriani and Sidik (2020), Laurens et al (2017), Zakaria and Syamaun (2017), Arsaythamby and Zubainur (2014), Hidayat and Iksan (2015), and Lestari and Surya (2017) showed that achievements or mathematical activities for those taught using realistic mathematic education are higher than those in the control group.…”
Section: Resultssupporting
confidence: 85%
“…So the students' mathematical concept understanding ability becomes better. In line with the results of Purwati (2020) and Arnellis et al (2020) showed that the use of RME can improve student learning outcomes. Strengthened by some research results according to Tamur, Juandi, and Adem (2020), Febriani and Sidik (2020), Laurens et al (2017), Zakaria and Syamaun (2017), Arsaythamby and Zubainur (2014), Hidayat and Iksan (2015), and Lestari and Surya (2017) showed that achievements or mathematical activities for those taught using realistic mathematic education are higher than those in the control group.…”
Section: Resultssupporting
confidence: 85%
“…A realistic approach to mathematics, according to the findings, has an effect on learning achievement. These findings agree with those of Arnellis et al, who discovered that this method improves calculus learning [23].…”
Section: Methodssupporting
confidence: 93%
“…Arnellis et al found that a realistic mathematics education approach influenced high school students' calculus learning achievement [23]. The purpose of this study is to see how it affects elementary school student achievement.…”
Section: Introductionmentioning
confidence: 91%
“…Padahal matematika merupakan salah satu cabang ilmu yang penting (Tseng, Chang, Lou, & Chen, 2013;Irawan & Surya, 2017). Matematika adalah ilmu yang membutuhkan kemampuan berpikir tinggi (Arnellis, Fauzan, Arnawa, & Yerizon, 2020) karena itu, pada beberapa materi yang menggunakan banyak rumus mengharuskan peserta didik untuk memahami rumus-rumus tersebut untuk digunakan dalam memecahkan masalah dalam soal.…”
Section: Pendahuluanunclassified